Os efeitos da idade sobre o padrão de assimetrias táteis, visuais e hemiespaciais em destros e canhotos - LIMA, Fábio Djan Oliveira de (2008)
When bisecting horizontal lines, normal individuals tend to err leftwards of the true center, or zero point, a phenomenon known as "pseudonegligence. Previous clinical investigations indicated that lestions in the inferior portion of the right hemisphere parietal lobe impaired mechanisms controling the allocation of attention to the left side of extracorporal space. In addition, heminegligence was not restricted to the visual system, and has been observed in certain tactile and motor modalities as well. In this context, studies have shown that changes in manual preference and proficiency were also related to aging. At present, explanations for these age-realted trends have been incorporated into three alternative hypotheses: differential hemispheric deterioration, bilateral deterioration, and invariant asymmetry. In this study, data were obtained for 61 individuals of both sexes, right- and left-handers, in three age groups: 18 to 30 year olds, 35 to 55 year olds, and a group at age level 60 and above. Individuals were assessed on the Lateral Preference Inventory, the Tactile Line Bisection Test (TLBT), and the Visual Line Bisection Test (VLBT), and we sought to ascertain whether manual, visual, tactile and hemispatial performance would vary as a function of handedness and age. On the TLBT there were few significant differences from the zero point, trends were weak, inconsistent, and not related to handedness or age. The interdependence activation hypothesis as proposed by Bowers and Heilman was not supported, and in conclusion, this version of the TLBT was considered to be unreliable. In contrast, in response to the VLBT, pseudonegligence ocorred consistently in all of the groups. There was a significant interaction between hand and hemispace in all groups, especially when the left-hand divided lines in the left and central fields, a finding that supported the activation hypothesis. There were no significant differences between right- and left-handers, and no reliable trends across the age levels in either group. In sum, there was no evidence indicating the presence of early right hemisphere deterioration, because pseudonegligence also was also robust among the oldest groups. This finding lends more cogent support to the invariant asymmetry hypothesis.